2022
DOI: 10.1186/s41927-022-00293-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of thyroid dysfunction and autoimmune thyroid disease in patients with rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is one of the most common chronic non-organ-specific autoimmune diseases; meanwhile, autoimmune thyroid disease (AITD) is the most common organ-specific autoimmune disease that can lead to hypo or hyperthyroidism. Although the etiology of both diseases is complex with a combination of genetic and environmental factors, there are overlaps in genes contributing to the pathogenesis of both diseases. Numerous studies found a correlation between thyroid abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…They examined 35,708 cases of patients in terms of possible coexistence of RA and thyroid disorders, confirming the high incidence of AID, especially hypothyroidism, in this group of patients. Bagherzadeh-Fard et al [8] also found that there were twice as many cases of AITD coexistence with RA as in a control group.…”
Section: Rheumatoid Arthritismentioning
confidence: 89%
“…They examined 35,708 cases of patients in terms of possible coexistence of RA and thyroid disorders, confirming the high incidence of AID, especially hypothyroidism, in this group of patients. Bagherzadeh-Fard et al [8] also found that there were twice as many cases of AITD coexistence with RA as in a control group.…”
Section: Rheumatoid Arthritismentioning
confidence: 89%
“…Research shows that the STAT4, HLA-DRB1 genes and vitamin D receptors (present in B and T lymphocytes) play a particularly important role in the development of both diseases. A correlation between the occurrence of a positive anti-TPO antibody titer and the exacerbation and more severe clinical course of RA has also been documented [46,47]. Type 1 diabetes is a metabolic disorder associated with the destruction of insulin-producing pancreatic β cells by autoantibodies.…”
Section: Hashimoto's Thyroiditis and Other Autoimmune Diseases -T1d R...mentioning
confidence: 98%
“…They found that post-thyroidectomy TPOAb levels decreased from a mean of 339 to 59 IU/L, and there were major improvements in patients’ associated autoimmune features including RA [ 61 ]. These common and overlapping immune activation pathways may help to explain the reported exacerbation of disease activity in patients with an RA and AITD overlap [ 62 , 63 ].…”
Section: Effect Of Aitd On Ra Disease Activitymentioning
confidence: 99%